Efforts to Improve Writing Skills of Grade 1 Students through Picture Word Cards at SD Negeri 7 Bandar Baru - Ruslaini; Nurrahmi (DEEP LEARNING: Journal of Educational Research, 2025)
Motivated by the low writing skills of students as evidenced by the lack of Minimum Completeness Criteria (KKM) scores, writing learning in grade 1 of SD Negeri 7 Bandar Baru is conventional where students have not played an active role in teaching and learning activities. Learning is still centered on the teacher (central teaching). Picture word card media is one of the alternative actions in order to improve siwa writing skills. The purpose of this class action research is to determine the improvement of writing skills of grade 1 students of SD Negeri 7 Bandar Baru through the use of illustrated word card media. This research was carried out for 3 months, starting from September to November 2021. The data source came from 1st grade students of SD Negeri 7 Bandar Baru who had participated in learning using the medium of picture word cards. The data collection tools in this study are in the form of written tests and observation sheets. The validation of the data obtained was analyzed by comparing the average score with the assessment results. Data analysis with percentage descriptive statistics. The assessment procedure consists of two cycles. Each cycle consists of planning, implementation, observation and reflection. The results of the study showed that there was a very significant increase in student learning completeness from 43.59% in the initial condition before the application of the picture word card media to 92.30% at the end of cycle II after the research was carried out.